Digital Tool Integration in Hybrid Learning: Examining Pedagogical Practices through TPACK in a Private Islamic Higher Education Institution - Abdul Azizul Hakim; Irfan Azim (International Journal of Educational Qualitative Quantitative Research, 2026)
The integration of digital tools in hybrid higher education has become a defining pedagogical challenge in the post-pandemic era; however, private Islamic higher education institutions in developing contexts remain significantly underrepresented in the global literature. Grounded in the Technological Pedagogical Content Knowledge (TPACK) framework, this study examines how digital tools are integrated into pedagogical practices within a multi-program private Islamic higher education institution in Indonesia operating a proprietary Learning Management System (LMS) across fully online, face-to-face, and hybrid delivery modes. Adopting a mixed-methods, descriptive-evaluative case study design, data were gathered through an LMS platform documentary analysis, a structured questionnaire administered to 30 lecturers (Cronbach's α = 0.84), and semi-structured interviews with eight key academic informants. Quantitative results revealed a high overall level of faculty perception regarding digital tool integration (M = 4.01, SD = 0.71), with perceived pedagogical impact scoring the highest (M = 4.20). Qualitatively, thematic analysis yielded four dominant dimensions: the LMS as a pedagogical enabler, digital attendance as an accountability mechanism, persistent integration barriers, and hybrid learning as an evolving institutional identity. Crucially, the convergent integration of these data strands culminated in a novel six-layer model of technology-enhanced pedagogical practice, introducing a "periphery-to-center" TPACK adoption trajectory. This model offers a theoretically grounded developmental dynamic tailored specifically to resource-constrained, faith-based higher education institutions. The study underscores the critical necessity for structured faculty development programs and formalized institutional hybrid policies to successfully optimize LMS-mediated pedagogical transformation.